(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
The article examines some aspects of the introduction and development of innovations in commercial banks of the Republic of Uzbekistan based on the study of advanced experience of developed countries, and examines the scientific and theoretical views of foreign economists on banking innovations. Consequently, scientific conclusions, proposals and recommendations on the introduction and development of innovations in commercial banks of Uzbekistan were formed.